The curious transference of sensations in the ‘mismatched-palm’ rubber hand illusion - Nicholas Christos; Jen Mulholland; Margaret O’Leary; Rebekah C. White (i-Perception)
We describe a disconcerting illusion. The participant looks at the palm of a left rubber hand being touched while receiving synchronous touch on the back of their own hidden right hand. Despite postural incongruence, mismatching handedness and touch being at a different location on the viewed and hidden hands, participants experience the illusion of ownership of the rubber hand and the illusion of feeling touch on the rubber hand. The robustness of the rubber hand illusion to seemingly profound incongruencies is explained with reference to Riemer et al.’s four basic principles for successful embodiment.